Study of the Relation Between the Incidence of Ascite Syndrome and the Ventilation Factor in Broiler Chickens of the Broiler House - Feizi, Adel; Nazeri, Mehrdad (International Journal of Poultry Science, 2011)
The main objective of this study was to determine the relation between the incidence of ascites syndrome and the ventilation factor in broiler chickens in the northwest region of Iran. We studied seven flocks which showed ascites syndrome. We started to correct unsuitable ventilation conditions in all seven poultry houses. After correction of the ventilation conditions, the incidence rate of ascites syndrome decreased by 1% in all seven poultry houses and we could nearly reduce the prevalence of CRD complex from 7% to 1% in these flocks too.